2022
DOI: 10.1051/0004-6361/202142931
|View full text |Cite
|
Sign up to set email alerts
|

Solis

Abstract: Context. Protostellar jets are an important agent of star formation feedback, tightly connected with the mass-accretion process. The history of jet formation and mass ejection provides constraints on the mass accretion history and on the nature of the driving source. Aims. We characterize the time-variability of the mass-ejection phenomena at work in the class 0 protostellar phase in order to better understand the dynamics of the outflowing gas and bring more constraints on the origin of the jet chemical compo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Both models produce a garden-hose effect, resulting in jet wiggling (Raga et al 1993). The observed MMS 1 jet morphology allows us to distinguish the origin of the jet wiggling (Frank et al 2014;Schutzer et al 2022, and references therein). In the case of jet wiggling due to binary orbital motion, the jet is expected to bend in the direction opposite to the location of the secondary (binary) component.…”
Section: Jet Precessionmentioning
confidence: 90%
“…Both models produce a garden-hose effect, resulting in jet wiggling (Raga et al 1993). The observed MMS 1 jet morphology allows us to distinguish the origin of the jet wiggling (Frank et al 2014;Schutzer et al 2022, and references therein). In the case of jet wiggling due to binary orbital motion, the jet is expected to bend in the direction opposite to the location of the secondary (binary) component.…”
Section: Jet Precessionmentioning
confidence: 90%
“…The physical processes in the molecular outflow of core MM1#8 could be different from those of the intermediatemass Cepheus E core, which was recently studied with CO observations and numerical simulations (de Schutzer et al 2022;Rivera-Ortiz et al 2023). Rivera-Ortiz et al (2023) showed that one-velocity ejection variations successfully reproduce the observed features, especially the bimodal distribution of the dynamical timescales of the knots.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A series of these velocity spurs composes a jagged PV profile sometimes called the "Hubble wedge" (Arce & Goodman 2001). These complex PV diagrams have been investigated in about a dozen low-mass Class 0 protostars so far, including HH111 (Cernicharo & Reipurth 1996), L1551 (Bachiller et al 1994), L1157 (Gueth et al 1998), HH212 (Lee et al 2006), HH46-47 (Arce et al 2013), and more recently Cepheus E (de Schutzer et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation